X-Linked Immunodeficient Mice Exhibit Enhanced Susceptibility to Cryptococcus neoformans Infection - Wendy A. Szymczak (American Society for Microbiology, 2013)
ABSTRACT Bruton’s tyrosine kinase (Btk) is a signaling molecule that plays important roles in B-1 B cell development and innate myeloid cell functions and has recently been identified as a target for therapy of B cell lymphomas. We examined the contribution of B-1 B cells to resistance to Cryptococcus neoformans infection by utilizing X-linked immunodeficient (XID) mice (CBA-CaHN-XID), which possess a mutation in Btk. XID mice had significantly higher brain fungal burdens than the controls 6 weeks after infection with C. neoformans strain 52D (CN52D); however, consistent with the propensity for greater virulence of C. neoformans strain H99 (CNH99), CNH99-infected XID mice had higher lung and brain fungal burdens than the controls 3 weeks after infection. Further studies in a chronic CN52D model revealed markedly lower levels of total and C. neoformans-specific serum IgM in XID mice than in the control mice 1 and 6 weeks after infection. Alveolar macrophage phagocytosis was markedly impaired in CN52D-infected XID mice compared to the controls, with XID mice exhibiting a disorganized lung inflammatory pattern in which Gomori silver staining revealed significantly more enlarged, extracellular C. neoformans cells than the controls. Adoptive transfer of B-1 B cells to XID mice restored peritoneal B-1 B cells but did not restore IgM levels to those of the controls and had no effect on the brain fungal burden at 6 weeks. Taken together, our data support the hypothesis that IgM promotes fungal containment in the lungs by enhancing C. neoformans phagocytosis and restricting C. neoformans enlargement. However, peritoneal B-1 B cells are insufficient to reconstitute a protective effect in the lungs. IMPORTANCE Cryptococcus neoformans is a fungal pathogen that causes an estimated 600,000 deaths per year. Most infections occur in individuals who are immunocompromised, with the majority of cases occurring in those with HIV/AIDS, but healthy individuals also develop disease. Immunoglobulin M (IgM) has been linked to resistance to disease in humans and mice. In this article, we found that X-linked immunodeficient (XID) mice, which have markedly reduced levels of IgM, were unable to contain Cryptococcus in the lungs. This was associated with reduced yeast uptake by macrophages, an aberrant tissue inflammatory response, an enlargement of the yeast cells in the lungs, and fungal dissemination to the brain. Since XID mice have a mutation in the Bruton’s tyrosine kinase (Btk) gene, our data suggest that treatments aimed at blocking the function of Btk could pose a higher risk for cryptococcosis.